Effect of Scarification with Shallot (Allium cepa L. var. ascalonicum) Extract on Percentage and Germination Rate of Cat's Eye Seeds (Dimocarpus longan var. malesianus Leenh) - Elisa Herawati; Herijanto Thamrin; Agustina murniyati; Suwarto Suwarto; M. Fadjeri (JURNAL AGRIMENT, 2025)
Food security is a global challenge due to the heavy reliance on staple food commodities. Diversifying food sources based on local tropical plants is one of the key strategies to address this issue. The mata kucing fruit (Dimocarpus longan var. malesianus Leenh.), an endemic plant of Kalimantan, has the potential to be developed as an alternative food source. This study aimed to determine the effect of seed soaking duration in red onion (Allium cepa L. var. ascalonicum) extract on the germination percentage and rate of D. longan var. malesianus. A Completely Randomized Design (CRD) with a single factor was used, consisting of four treatments (P0, P1, P2, and P3) with 30 replications for each treatment. This study shows a positive biological response to scarification treatment with shallot extract (P1, P2, P3) on the percentage and rate of germination of Dimocarpus longan var. malesianus seeds compared to the control (P0). However, the results of the ANOVA analysis show that the differences between treatments are not statistically significant. These findings indicate that the duration of immersion and the concentration of shallot extract used in this study have not yet reached the optimal level to produce a significant increase in germination effectiveness. Keywords: sDimocarpus longan var. malesianus, shallot extract (Allium cepa L.), germination percentage, germination rate